Open suturectomy management in craniosynostosis of bilateral coronal and metopic suture - Marthinson Andrew Tombeng; I Wayan Niryana (Indoscholar, 2021)
Craniosynostosis is a cranial deformation that is characterized by the premature fusion of one or more of the cranial sutures. Synostosis of multiple suture is a rare case and can be treated with open suturectomy procedure which is one of the surgical management by removing the fused suture with the purpose to allow the constricted area to expand with the growing brain. We present a case of a 2-month-old male infant with abnormal head shape since birth with a non-contrast 3D computed tomography (CT) scan of the head confirmed closure of the bilateral coronal and metopic suture. Open suturectomy was performed with no post operative complications. Open suturectomy technique can be performed in the management of multisutural craniosynostosis as indicated. The diagnosis of which suture are affected, the timing of surgery, and the prevention of surgical complication such as excessive blood loss are the important factors need to be considered.